Sustainable environmental goals of the European Union with respect to improvement of environmental protection in the EU - Siliņa, Betija (Riga Graduate School of Law, 2020)
Significantly depleting natural resources and continuously damaged environment has changed the overreaching goal of the EU policies, legislation, and development, and it is – sustainable development. Sustainable development aims at building an economy that meets the needs of present without jeopardizing the needs of future. One of the fundamental constituting criteria of sustainable development is environmental protection. Environmental protection has been one of main objectives in international environmental agreements, as well EU legal instruments. Once European Union adopted Environmental Liability Directive 2004/35/EC, invoking the ‘polluter-pays’ principle, to prevent and remedy environmental damage, it was set that businesses are not operating sustainably and they cause environmental damage, which costs are often borne by society as a whole. Main objective for the research is to examine how could potential sustainable development concepts and instruments contribute to better environmental protection and therefore implementation and application of Environmental Liability Directive. Additionally, thesis discusses how it could minimize society and companies costs to restore damaged environment. The author provides an answer to the proposed research question through examination of EU environmental law principles, framework and implementation of Environmental Liability Directive and EU sustainable policy and instrument frameworks, analysis, and proposed instruments to achieve sustainable environmental goals.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Environmental law